Robotic excavation in construction automation. - Quang Ha (IEEE Robotics and automation magazine)
This article presents some results of the autonomous excavation project conducted at the Australian Centre for Field Robotics (ACFR) with a focus on construction automation. The application of robotic technology and computer control is one key to construction industry automation. Excavation automation is a multidisciplinary task, encompassing a broad area of research and development. The ultimate goal of the ACFR excavation project is to demonstrate fully autonomous execution of excavation tasks in common construction, such as loading a truck or digging a trench. A number of difficult theoretical and practical problems must be solved to achieve this objective. The problems fall into three main groups: excavation planning, sensing and estimation, and control